A comparative study of the modification of gold and glassy carbon surfaces with mixed layers of in situ generated aryl diazonium compounds - Liu, G.; Chockalingham, M.; Khor, S.M.; Gui, A.L; Gooding, J.J. (2010)
In situ generated aryl diazonium cations were synthesized in the electrochemical cell by reaction of the corresponding amines with NaNO in aqueous HCl. This paper reports a study of the formation of mixed layers from in situ generated aryl diazonium cations. Firstly, glassy carbon (GC) and gold electrode surfaces were modified with five single in situ generated aryl diazonium salts to obtain their corresponding reductive potential followed by the modification of GC and gold surfaces with eight binary mixed layers of in situ generated aryl diazonium salts. The difference between GC and gold surfaces in terms of in situ formation of two-component aryl diazonium salt films was compared. The behavior of the mixed layers formed from in situ generated aryl diazonium salts relative to diazonium salts that were pre-synthesized prior to surface modification was also investigated. Cyclic voltammetry and X-ray photoelectron spectroscopy were used to characterize the resulting modified GC and gold surfaces. It is found that for some aryl diazonium salts the potential at which reductive adsorption is achieved on gold and GC surfaces is significantly different. For the eight sets of binary mixed layers, the species with more anodic potential are more difficult to attach to the both GC and gold surfaces. The behavior of the mixed layers formed from in situ generated aryl diazonium salts and the pre-synthesized diazonium salts is similar; which emphasizes the advantage of the in situ approach without any apparent difference in behavior to the presynthesized diazonium salts.